EFFECT OF SEA CUCUMBER OIL AND HONEY IN POST RADIOTHERAPY NASOPHARYNGEAL CARCINOMA PATIENTS - Wawan Hendrawan; Bogi Soeseno; Tonny Basriyadi S; Yussy Afriani Dewi; Ade Burhanuddin (TALENTA PUBLISHER, 2020)
Abstract Introduction: Nasopharyngeal carcinoma is one of the most commonly found cases of head and neck malignancy. The most common side effects of radiotherapy is skin damaged. Until now, there is no standard therapy that has been given to post radiotherapy patient in Hasan Sadikin Hospital. Sea cucumber and honey can accelerate the healing process of the wound caused by radiotherapy. Objective: This study was conducted to compare the effects of the use topical sea cucumber oil and honey in patient with nasopharyngeal carcinoma post radiotherapy. Method: The study was conducted at Radiotherapy Clinic in Hasan Sadikin Hospital from may until September 2015 with patients who experienced skin damaged level two or more based on the criteria of Radiation Therapy Oncology Group (RTOG). This was an experimental study. Subjects were selected consecutively between the two groups: sea cucumber oil group and honey group. The draft analysis was done using Randomized Controlled Trial (RCT). Result: 30 patients were divided equally into two groups, sea cucumber group and honey group. Most of the nasopharyngeal carcinoma patients were >45 years old, the ratio man to woman was 2-3:1, with the BMI was <18.5. All subjects in this study experienced recovery rate up to level 1 (p=1.0), after one week of treatment. In the 2nd week after treatment all patients in the sea cucumber group achieved recovery up to level 0, and in the honey group as much as 2 patients only experienced the recovery rate to level 0, while the remaining 13 subjects remained at level 1 (p=0.0001). It was found that the wound healing process occurs better in sea cucumber oil group than the honey group (p=0.0001). Conclusion: Sea cucumber oil accelerates the healing process of the skin tissue damaged in patients with nasopharyngeal carcinoma after radiotherapy, faster than with honey.